Bile duct injury in an anatomical variant of the posterior right hepatic duct draining in the cystic duct: case report - Yamamoto-Moreno, José Adrián; Gómez-Fernández, Ricardo; Iturbide-Aguirre, Alejandro Steven; Hernández-Sánchez, Jessica; Cutipa-Flores, Gainsborough Gonzalo (International Journal of Research in Medical Sciences, 2022)
During laparoscopic cholecystectomy, several factors increase the likelihood of bile duct injury (BDI). The most common cause of BDI during laparoscopic cholecystectomy is an inappropriate identification of the critical view of safety associated with acute and chronic inflammation, obesity, haemorrhage, and anatomical variants. Of all anatomic variants of the biliary tree, Blumgart type F has been reported as the least common, but allegedly it carries the biggest risk of BDI. We present the case of a 45-year-old woman with acute cholecystitis subjected to laparoscopic cholecystectomy with Strasberg type C injury in association with a Blumgart F variation confirmed by magnetic resonance cholangiopancreatography. The anatomical variant was identified during the surgical procedure but the BDI was diagnosed postoperatively. Intraoperative identification and treatment of the injury confers a better prognosis to the patient. Management of a BDI on a Blumgart F variant can be challenging and must be targeted to the individual case. Safety measures to prevent such injuries must be promoted by institutions.